Identificación y análisis de procesos de producción en la finca perteneciente a la empresa Florícola Agrorab CIA. LTDA. ubicada en la provincia de Cotopaxi, cantón Pujilí, propuesta de mejora en los procesos de producción – año 2014 - Jiménez Vizuete, Carlos Eduardo (2016)
This research is about the identification and analysis of production processes in the flower farm AGRORAB Cia. Ltda., which is located in the Cotopaxi province, with this movement and time analysis. It would reduce the downtime by studying different flowcharts. This company has an adequate infrastructure and optimal technology, in so far as to entire production process is concerned, but it can be seen that still indicate some shortcomings on Carnation production process. As such, there is a delay in harvesting, transporting, postharvest, the cold storage and transport freighters….